Investigating the effect of fuel cetane number, oxygen content, fuel density, and engine operating variables on NOx emissions of a heavy duty diesel engine. Issue 1 (19th August 2016) - Singh, Devendra; Subramanian, K.A.; Juneja, Manav; Singh, Kalyan; Singh, Sathpal; Badola, R.; Singh, Nishan
Abstract : Biodiesel is a promising alternative fuel for compression ignition (CI) engine, but the nitrogen oxide (NOx) liability associated with it is a major challenge. NOx emissions are affected by both engine technology and fuel properties. Experimental studies were conducted on an unmodified heavy‐duty direct injection diesel engine to analyze the effect of fuel properties such as cetane number (CN), oxygen content, fuel density, and engine operating variables (speed and load) on NOx emissions. Test results revealed that NOx concentration is directly proportional to engine load and to biodiesel percentage in blends, and is inversely related to engine speed. Fuel‐bound oxygen in the blended fuels are mainly responsible for the higher NOx. An empirical correlation was developed to predict NOx concentration as a function of CN, oxygen content, fuel density, speed, and load. Experimental and predicted values of NOx emission concentrations for two blends, BA25 and BA50 (25% and 50% microalgae biodiesel blended with diesel), at 2205 rpm and 100% load are 723.19 and 722.94 ppm, and 749.89 and 791.12 ppm, respectively. The developed correlation will be useful in estimating the NOx emissions of a CI engine fueled with various other oxygenated biofuels at different speeds and loads. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 214–221, 2017